2014
DOI: 10.1007/s11011-014-9550-3
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of matrix metalloproteinase-9 gene decreases cerebrovascular permeability and fibrinogen deposition post traumatic brain injury in mice

Abstract: Traumatic brain injury (TBI) is accompanied with enhanced matrix metalloproteinase-9 (MMP-9) activity and elevated levels of plasma fibrinogen (Fg), which is a known inflammatory agent. Activation of MMP-9 and increase in blood content of Fg (i.e. hyperfibrinogenemia, HFg) both contribute to cerebrovascular disorders leading to blood brain barrier disruption. It is well-known that activation of MMP-9 contributes to vascular permeability. It has been shown that at an elevated level (i.e. HFg) Fg disrupts blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
107
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(121 citation statements)
references
References 72 publications
11
107
1
Order By: Relevance
“…Brain pial microcirculation was prepared for observations according to the method described previously (Muradashvili et al . a , b , c , ). Briefly, a mouse was placed on a stereotaxic apparatus (World Precision Instruments, Sarasota, FL, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Brain pial microcirculation was prepared for observations according to the method described previously (Muradashvili et al . a , b , c , ). Briefly, a mouse was placed on a stereotaxic apparatus (World Precision Instruments, Sarasota, FL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…), were used in combination to define the formation of caveoli in the vessels of brain samples as described previously (Muradashvili et al . a , c ; ). Fluorescence intensity was measured in AOI along the vessel wall and data were normalized by the length of the respective vascular segment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical TBI models with MMP-9 inhibition (including SB-3CT, a highly selective MMP-2 and MMP-9 inhibitor) have shown improvement in BBB integrity (from reduced tight junction protein degradation and decreased vascular permeability) attenuated microglial activation, and reduced lesion volume; the effect on outcome has been controversial [145, 185-190]. In part, this may be due to the involvement of MMP-9 in neurovascular modeling and repair [124, 191]; timing of MMP-9 inhibition may thus be critical in terms of impact on edema and outcome.…”
Section: Molecular Pathophysiology Biomarkers and Targeted Treatmenmentioning
confidence: 99%
“…Furthermore, our group has demonstrated that hyperhomocysteinemia enhanced cerebrovascular permeability through activation of MMP-9 and increased the formation of fibrinogen-β-amyloid complex within the brain (42). Additionally, increased cerebrovascular permeability and memory loss was also observed with increased MMP-9 activity which was ameliorated by MMP-9 ablation (43). …”
Section: Types Of Mmps and Their Involvement In Diseasesmentioning
confidence: 99%